2009
DOI: 10.1080/15567030802087528
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics of Sunflower Oil Methyl Ester

Abstract: In this study, use of sunflower oil methyl ester as an alternative fuel in a 4 stroke turbo diesel engine with 4 cylinders, direct injection, and 55 kW power was analyzed. The engine has been fueled by diesel fuel and biodiesel (B100) obtained from methyl ester of sunflower oil and by running the test engine with 14 different speeds and full load, the results have been analyzed. Smoke emissions obtained in biodiesel use were slightly less, which could be attributed to better combustion efficiency. Also, HC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…The lower speeds increase the AFR and render the mixture within the combustion chamber leaner. Similarly, with all fuels and at any speed the CO emissions from the exhaust are augmented when the engine operates under higher loads, a trend that has also been reported in the literature [44,49,50]. As is generally true for ICEs, increasing the engine load initially results in a richer mix (with lower AFR).…”
Section: Nox Emissionssupporting
confidence: 62%
See 1 more Smart Citation
“…The lower speeds increase the AFR and render the mixture within the combustion chamber leaner. Similarly, with all fuels and at any speed the CO emissions from the exhaust are augmented when the engine operates under higher loads, a trend that has also been reported in the literature [44,49,50]. As is generally true for ICEs, increasing the engine load initially results in a richer mix (with lower AFR).…”
Section: Nox Emissionssupporting
confidence: 62%
“…The combustion reaction in a CI engine comprises two pathways-the breakdown of the fuel to form CO, and the oxidation of CO to form CO 2 -with most of the fuel's energy liberated in the second process. The factors that determine the CO emissions from a CI engine include the fuel-air mixture features (such as the air-fuel ratio (AFR), mixing condition, and fuel type), engine operating conditions (such as speed, load, fuel atomization, and injection parameters including timing, duration, and pressure), and engine specifications (such as compression ratio and combustion chamber design) [44,45]. Of these, the AFR has the largest influence on the production of CO emissions and can be seen as the prime driver of CO production, while the other factors enhance its effects.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…This is due necessity of rich mixture with increase in load to sustain steady power output. Ulusoy et al (2009) found increase in CO emission with increase in load citing decrease in air fuel ratio at higher loads as the cause. By adding magnetite to RBOME, 6.34% reductions in HC emissions were observed.…”
Section: Error Analysismentioning
confidence: 95%
“…Bu ülkeler arasında en fazla üretim yapan Almanya 4 milyon ton kurulu ve 2,7 milyon ton üretim kapasitesine sahiptir. Yine Almanya'da biyodizel kullanımının toplam dizel yakıtı kullanımındaki oranının % 7-8 civarında olduğu görülmektedir (Bockey, 2014 (Ulusoy, 2009). AB adayı ülke olarak Türkiye'de söz konusu Direktife uyumun sağlanmasında gerek ülkenin biyodizel üretim kapasitesinin kullanılamıyor olması ve gerekse ciddi manada çevre kirliliğine neden olan atık yağların kontrolü yönetmeliğine adaptasyonun sağlanabilmesi gereklidir.…”
Section: Gġrġġunclassified